The Effect of Accounting Understanding, Education Level, Business Length and Business Size on the Application of Financial Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) on MSMEs in Binawidya District, Pekanbaru City - Nur Rohmannisa, Afifah; Syafei, Jasmina; Nurcahaya (MUI Kota Pekanbaru, 2025)
This study aims to see how far the influence of understanding accounting, understanding of accounting, level of education, length of business and business size on the application of SAK EMKM to MSMEs in Binawidya District, Pekanbaru City. This study uses quantitative methodology with primary data collection obtained from respondents through questionnaires. The population in this study is all MSME actors in Binawidya District. iSample research method using Purposive Sampling method, The sample in this study is iMSME business actors as many as i 255 businesses. By using PLS and SmartPLS 4.0.9.6, analyze the relationship between dependent and independent variables. The findings of this study show that accounting understanding, education level, length of business and business size have a significant effect on the application of SAK EMKM to MSMEs in Binawidya District, Pekanbaru City.